Local Wisdom Used Wildlife Behavior as Indicators of Natural Phenomenon in Maluku Small Islands - Imanuel Kaya; Ernywati Badaruddin; Ivonne R G Kaya (Pattimura University Ambon Maluku Indonesia, 2022)
The people of Maluku, since their ancestors, have been known as a society with various social institutions which are, in fact, very appreciative of the living and non-biological natural resources around them. It has caused some historians to argue that the Maluku people are religious people oriented toward the nature surrounding their lives. The various forms of